SPE Annual Technical Conference and Exhibition 2008
DOI: 10.2118/116719-ms
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Response Surface Based Model for Minimum Miscibility Pressure (MMP) Correlation of CO2 Flooding

Abstract: Correlations are commonly used to predict CO2 multiple contact miscibility (MMP) since such correlations are generally inexpensive and easy to use. In this study, we used a novel approach based upon four dimensionless scaling groups commonly used for hydrocarbon phase behavior modeling (reduced temperature and acentric factors for light and heavy pseudo components) as well as multivariate regression analysis based on response surface methodology to develop an MMP correlation for a broad range of reservoir oils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Obviously, a response surface can be constructed in different ways, e.g., can be constructed directly on dense Cartesian grid of input parameters with a much higher computational efforts. In that way, the response surface methodology has been applied, e.g., to design an experiment for CO 2 miscibility behavior in [9]. In the current paper, we also would like to explore methodology which demands minimum number of model evaluation to construct response surface (see Section 2.3).…”
Section: Stochastic Response Surface Methodsmentioning
confidence: 99%
“…Obviously, a response surface can be constructed in different ways, e.g., can be constructed directly on dense Cartesian grid of input parameters with a much higher computational efforts. In that way, the response surface methodology has been applied, e.g., to design an experiment for CO 2 miscibility behavior in [9]. In the current paper, we also would like to explore methodology which demands minimum number of model evaluation to construct response surface (see Section 2.3).…”
Section: Stochastic Response Surface Methodsmentioning
confidence: 99%
“…In order to simulate slim tube performance by artificial neural network, there are many parameters which have effect on MMP directly. They include reservoir temperature, oil characteristics, and injected gas composition (Metcalfe et al, 1973;Huang et al, 2003;Emera and Sarma, 2005;Ghomian and Sepehrnoori, 2008). Of course, this data is in PVT test reports for hydrocarbon components (C1-C 7 + : including 9 components) and non-hydrocarbon components (N2, H2S, CO2).…”
Section: Development Of a New Artificial-neural-network Modelmentioning
confidence: 99%
“…These experimental data are needed to tune the EOS model of properly characterized fluid. Besides, simulation of 1-D slim tube is also computationally expensive since different simulation cases (at various pressure conditions) have to be carried out (Haajizadeh et al, 2006;Zhao, 2006;Ghomian, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Table summarizes the current predictions and correlations related to MMP. Table shows that the main factors affecting MMP are the reservoir fluid composition, injected gas, and reservoir temperature. Where reservoir temperature and injection gas are well-defined, MMP is primarily influenced by fluid composition. Numerous studies have shown that the influence of fluid composition on MMP depends on its molecular weight. , Consequently, a significant number of correlations between MMP and properties of crude oil have been developed in the past few decades.…”
Section: Introductionmentioning
confidence: 99%